Stress Response of four Common Carp (Cyprinus carpio L.) Varieties with Different Genetic Background - Kormos, Balázs (Acta Agraria Debreceniensis, 2003)
Four different carp varieties were tested for stress reaction, with the help of 10 °C cooling and 100 g/l crowding. The selected varieties represented a broad genetic spectrum of carp species. The stress was monitored by measuring plasma cortisol, glucose and lysozim levels. In each test different varieties showed significantly different reaction to stress. This means that they differ in the trait of general resistance. Thus, this trait can be used in selection programmes and the acquired information helps to understand fish-environment interaction and specific resistance. These traits should be used in selection to improve the breeding of new more tolerant species for intensive farming or for organic production.